The improved assembly of 7DL chromosome provides insight into the structure and evolution of bread wheat. Issue 3 (18th September 2019) - Feng, Kewei; Cui, Licao; Wang, Le; Shan, Dai; Tong, Wei; Deng, Pingchuan; Yan, Zhaogui; Wang, Mengxing; Zhan, Haoshuang; Wu, Xiaotong; He, Weiming; Zhou, Xianqiang; et al.
Summary: Wheat is one of the most important staple crops worldwide and also an excellent model species for crop evolution and polyploidization studies. The breakthrough of sequencing the bread wheat genome and progenitor genomes lays the foundation to decipher the complexity of wheat origin and evolutionary process as well as the genetic consequences of polyploidization. In this study, we sequenced 3286 BACs from chromosome 7DL of bread wheat cv. Chinese Spring and integrated the unmapped contigs from IWGSC v1 and available PacBio sequences to close gaps present in the 7DL assembly. In total, 8043 out of 12 825 gaps, representing 3 491 264 bp, were closed. We then used the improved assembly of 7DL to perform comparative genomic analysis of bread wheat (Ta7DL) and its D donor, Aegilops tauschii (At7DL), to identify domestication signatures. Results showed a strong syntenic relationship between Ta7DL and At7DL, although some small rearrangements were detected at the distal regions. A total of 53 genes appear to be lost genes during wheat polyploidization, with 23% (12 genes) as RGA (disease resistance gene analogue). Furthermore, 86 positively selected genes (PSGs) were identified, considered to be domestication‐related candidates. Finally, overlapping of QTLs obtained from GWAS analysis and PSGs indicated that TraesCS7D02G321000 may be one of the domestication genes involved in grain morphology. This study provides comparative information on the sequence, structure and organization between bread wheat and Ae. tauschii from the perspective of the 7DL chromosome, which contribute to better understanding of the evolution of wheat, and supports wheat crop improvement.